Hostile heartland: Racism, repression, and resistance in the Midwest - Campney, Brent M. S. (University of Illinois Press, 2019)
"We forget that racist violence permeated the lower Midwest from the pre-Civil War period until the 1930s. From Kansas to Ohio, whites orchestrated extraordinary events like lynchings and riots while engaged in a spectrum of brutal acts made all the more horrific by being routine. Also forgotten is the fact African Americans forcefully responded to these assertions of white supremacy through armed resistance, the creation of press outlets and civil rights organizations, and courageous individual activism. Drawing on cutting-edge methodology and a wealth of documentary evidence, Brent M.S. Campney analyzes the institutionalized white efforts to assert and maintain dominance over African Americans. Though rooted in the past, white violence evolved into a fundamentally modern phenomenon, driven by technologies such as newspapers, photographs, automobiles, and telephones. Other surprising insights challenge our assumptions about sundown towns, who was targeted by whites, law enforcement's role in facilitating and perpetrating violence, and the details of African American resistance."--Publisher's description.
Keywords: 1800-1899; 1900-1999; activisme; amériques; approches et analyses; cours; esclavagisme; his4443; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; résistance; systèmes d'oppressions; thématiques; violence coloniale; violences; violences raciales; états-unis; états-unis (sud)